Producer for "Paper planes, Don’t Always Soar": collaborative partnerships to amplify community change - Tan, Terry De Hao (Nanyang Technological University, 2023)
Inspired by a true story of an aviation disaster, a daughter tries to bridge the bond she lost after her father returns home from a plane crash, where he struggles to remember his life before that fateful catastrophe.